LINGUISTIC EXPRESSIONS IN COSMOPOLITAN MAGAZINE’S ADVERTISEMENT - Noor, Medyana; Agustien, Helena I.R.; ., Rohani (ELT Forum: Journal of English Language Teaching, 2017)
This study aimed at describing the way the advertiser used the distinctive linguistic expressions in the Cosmopolitan Magazine’s Advertisement. Since the advertisement should attract the consumer as many as possible, the advertiser needed to have a plan to find a solution of this problem in conveying the messages through the advertisement. In this study, the discussion was limited by finding out distinctive linguistic expressions of the advertisement which can be used to convey meanings through text and image. This was a descriptive qualitative study. The analysis involved context of situation analysis, lexicogrammar analysis, and semantic analysis. The analysis revealed that in terms of context of situation, the advertiser delivered persuasive text. Therefore, the advertiser is obliged to say persuasive statements to persuade the consumer or buyer. Meanwhile, lexicogrammar analysis showed that the advertiser delivered the message of the product in order to inform the benefit and achieve the economic goal of the advertised product. The large parts of the clauses of the text were positive adjective which showed the good quality of the advertised product. The semantic analysis showed that personification was the most frequent figure of speech used in the advertisement text. In that sense, the advertiser wanted to give the inanimate object the quality of living thing.